Development of micro-lens array for indoor optical wireless communication - Xu, Cong (2013)
Modulated white light LEDs can be used for simultaneous illumination and communication. This project is to develop a micro-lens array for receiving white light LED signals in indoor optical wireless communication system. [3rd Award]